2014
DOI: 10.1371/journal.pone.0113080
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Colonization Orchestrates TLR2 Expression, Signaling and Epithelial Proliferation in the Small Intestinal Mucosa

Abstract: The gut microbiota is an environmental factor that determines renewal of the intestinal epithelium and remodeling of the intestinal mucosa. At present, it is not resolved if components of the gut microbiota can augment innate immune sensing in the intestinal epithelium via the up-regulation of Toll-like receptors (TLRs). Here, we report that colonization of germ-free (GF) Swiss Webster mice with a complex gut microbiota augments expression of TLR2. The microbiota-dependent up-regulation of components of the TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 36 publications
2
90
1
Order By: Relevance
“…5C). Other than TLR4, TLR2 also activates MyD88-dependent signaling pathways and increases epithelial cell proliferation (36,41,42). Bacterial cell wall products, such as LTA and peptidoglycan, activate TLR2 signals upon initial binding to CD14 (43,44).…”
Section: Eritoran Exposure Inhibits Lps/tlr4-induced Cell Proliferatimentioning
confidence: 99%
“…5C). Other than TLR4, TLR2 also activates MyD88-dependent signaling pathways and increases epithelial cell proliferation (36,41,42). Bacterial cell wall products, such as LTA and peptidoglycan, activate TLR2 signals upon initial binding to CD14 (43,44).…”
Section: Eritoran Exposure Inhibits Lps/tlr4-induced Cell Proliferatimentioning
confidence: 99%
“…In contrast, transcript levels of TRIF were unchanged. 1 Furthermore, we found that TLR2 and TLR1 mRNA levels in the small intestine depend on the adaptor molecules MyD88 and TRIF. In our monocolonization model with the Escherichia coli K-12 strain JP 313, we found that specifically TLR6 mRNA levels were reduced after 14 d of colonization.…”
Section: Please Scroll Down For Articlementioning
confidence: 81%
“…We suggested that this is a route that supports renewal of the small intestinal epithelium through cell-intrinsic TLR2 signaling. 1 In this study we analyzed germ-free (GF) mice and mice deficient for bacterial signature sensing TLRs to explore how pattern recognition of gut microbial signatures may affect renewal of the small intestinal mucosa. [2][3][4] By decimation of gut microbial communities via administration of broad-spectrum antibiotics, 5 we demonstrated that microbiotadependent regulation of TLR2 is reversible.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…The initial composition and developmental trajectory of the microbiome may have a marked influence on host health status at a later stage in life [48,49]. Preclinical research suggests, for example, that appropriate microbial colonization of the GIT is critical for postnatal development [50] and normal neuronal excitability [51] in the ENS as well as epithelial proliferation [52].…”
Section: The Gut Microbiome As a Virtual Endocrine Organmentioning
confidence: 99%